THE EFFECT OF SOCIAL SUPPORT, SELF-EFFICACY, AND SELF-REGULATION ON ACADEMIC RESILIENCE - Marwah, Siti; Eryanto, Henry; Widyastuti, Umi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
Academic resilience is very necessary to face challenges at school so that students can adapt and recover from difficult situations. Various factors can influence a person's level of academic resilience, in this research the factors used are social support, efficacy and self-regulation. So, this research aims to find out whether there is an influence between social support, self-efficacy and self-regulation on academic resilience in students at SMKN 42 Jakarta. This research uses a quantitative approach with SEM-PLS testing with direct and indirect hypothesis testing. Sampling in this study used a proportional stratified random sampling technique with a total sample of 258 students at SMKN 42 Jakarta. Data collection used in this research was based on observation and filling out a questionnaire using a Likert scale. The research results show that the variables of self-efficacy and self-regulation have an influence on academic resilience with a statistical t value > 1.96 and a P-Values ​​< 0.05. The research results also show that social support indirectly influences academic resilience through the self-efficacy variable. Meanwhile, the social support variable has no effect on academic resilience.